Seroprevalence of infectious pathogens of zoonotic and veterinary importance in wild ruminants from Slovenia - Žele Vengušt, Diana; Krt, Brane; Blagus, Rok; Vengušt, Gorazd; Bandelj, Petra (Frontiers in Veterinary Science, 2024)
Wildlife represents an increasingly important source of pathogens of medical and veterinary importance. Surveillance in wildlife offers an insight on current epidemiological status of selected pathogens and help to prevent spillovers to humans and livestock. Our study included 312 wild ruminants belonging to five species: Roe deer (n=134), red deer (n=113), Alpine chamois (n=53), European mouflon (n=10) and Alpine ibex (n=2). Seven pathogens that may have profound effect on human/livestock health and economic viability of the farms were tested using serological methods. Antibodies against Toxoplasma gondii, Neospora caninum, Coxiella burnetii, Brucella spp., Chlamydophila abortus, Mycobacterium avium subsp. paratuberculosis (MAP) and Mycobacterium bovis were detected in 34.62% (108/312), 0.96% (3/312), 2.24% (7/312), 0%, 0.96% (3/312), 0%, 0.64% (2/312) of animals tested, respectively. Because of low prevalences, risk factors were assessed only for T. gondii. Sex (female>male) and species (roe deer>red deer, roe deer>Alpine chamois) were significantly associated with the T. gondii positive outcome, while age was not. Adult males had the lowest T. gondii prevalence which offers future research opportunities. The lower seroprevalence of most investigated pathogens suggests game meat, if properly cooked, as being relatively safe for human consumption. This is the first study investigating the seroprevalence and associated risk factors of selected pathogens in wild ruminants in Slovenia.